Teachers’ perception on the relationships between transformational leadership and school culture in primary cluster schools - Veeriah, Jeyasushma; Chua, Yan Piaw; Siaw, Yan Li; Hoque, Kazi Enamul (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2017)
Education is a key factor contributing to the success of a nation’s human development to support the national vision and mission. The nation depends on schools to ensure the efficient and successful education process for human development. In fact, studies on educational progress have proven that leadership is important for school success and high performance. The vast literature has supported that transformational leadership of school principals is the proven leadership attribute in school success and achievement. Thus, this study aims at examining the relationships between principals’ transformational leadership practices and school culture in primary cluster schools in the state of Selangor, Malaysia. A quantitative approach was used to achieve the aim. The study included 331 teachers in primary cluster schools in Selangor and data were analysed using SPSS v.22. The findings indicated that teachers in primary cluster schools in Selangor perceived their principals as having a high level of transformational leadership characteristics. Furthermore, a significantly positive and a strong correlation was found between principal transformational leadership practices and school culture. Multiple regression analysis showed that only four out of the eight dimensions of transformational leadership are statistically significant predictors of school culture. It is recommended that the education authorities and principals take note of the importance of transformational leadership in ensuring school success.